Study of gold-platinum and platinum-gold surface modification and its influence on hydrogen evolution and oxygen reduction - BRANIMIR N. GRGUR; LJILJANA M. VRACAR; MAJA D. OBRADOVIC; MAJA N. DESIC; MILICA M. POPOVIC (Journal of the Serbian Chemical Society, 2005)
Surface modification of the electrodes was conducted from sulfuric acid solutions containing the corresponding metalchloride complexes using cyclic voltammetry. Comparing the charges of the hydrogen underpotential deposition region, and the corresponding oxide reduction regions, it is concluded that a platinum overlayer on gold forms 3D islands, while gold on platinum forms 2D islands. Foreign metals present in an amount of up to one monolayer exert an influence on the change in reaction rate with respect to both hydrogen evolution (HER) and oxygen reduction (ORR) reactions. Aplatinum overlayer on a gold substrate increases the activity forHER and for ORR, compared with pure gold. These results can be understood in terms of a simple model, in which the change in the H and OH binding energies are directly proportional to the shift of the d-bond center of the overlayer. On the contrary, a gold layer on platinum slightly decreases the activity for both reactions compared with pure platinum.